2019
DOI: 10.1021/acs.iecr.9b01843
|View full text |Cite
|
Sign up to set email alerts
|

110th Anniversary: Recent Progress and Future Challenges in Selective Catalytic Reduction of NO by H2in the Presence of O2

Abstract: Over the past several years, selective catalytic reduction of NO x with hydrogen (H2-SCR) has been regarded as a promising technology for NO x abatement under lean-burn conditions. In this review, we discuss the recent progress in the development and understanding of H2-SCR catalysts. The various mechanisms that have been proposed in the literature are reviewed first. The influence of the catalyst chemical components (noble metals, supports, promoters, and perovskites) and their roles in H2-SCR are then anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 112 publications
0
39
0
2
Order By: Relevance
“…13,16 Recently, through several mechanistic studies, it has been found that the catalytic activity depends not only on the acidic and redox properties of the material, 10,17 but also on the metalsupport interactions. 18 In particular, the nature of the supported tungsten species is a determining factor. The reported conventional catalysts are normally prepared by uncontrolled impregnation, resulting in different species, including isolated surface tungsten sites, WxOy clusters, amorphous WO3 and Ce2(WO4)3.…”
Section: Introductionmentioning
confidence: 99%
“…13,16 Recently, through several mechanistic studies, it has been found that the catalytic activity depends not only on the acidic and redox properties of the material, 10,17 but also on the metalsupport interactions. 18 In particular, the nature of the supported tungsten species is a determining factor. The reported conventional catalysts are normally prepared by uncontrolled impregnation, resulting in different species, including isolated surface tungsten sites, WxOy clusters, amorphous WO3 and Ce2(WO4)3.…”
Section: Introductionmentioning
confidence: 99%
“…Except catalyst, these reactions are affected by the concentration of NO and O 2 in the feed gas stream [7][8][9], the temperature of reaction [10,11], water content [12,13], and sulfur, [14,15] etc. In these three technologies, the key step is the decomposition of adsorbed NO to produce adsorbed N 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a suitable catalyst should be selected to react methane with NO to increase the conversion rate of NO. In the H 2 -SCR process [9], oxygen preferentially reacts with H 2 to form water due to its lower energy barrier (∆H 0 = −242 kJ/molH 2 ) compared to the reaction of two NO molecules with four hydrogen molecules to form N 2 and water (∆H 0 = −574 kJ/molH 2 ), as shown in Equation (3). It results in poor activity and selectivity toward N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…achieved the NO reduction by H 2 over 1 %Pd‐5 %V 2 O 5 /TiO 2 ‐Al 2 O 3 , and a maximum NO conversion of 98 % was realized with N 2 selectivity up to 95 % at 150 °C. The Pt and Pd‐based catalysts exhibit outstanding catalytic activity in H 2 ‐SCR, while the Pd‐based catalyst possesses a better N 2 selectivity versus Pt contained component [8] …”
Section: Introductionmentioning
confidence: 99%